Why Nations Fail : The Origins of Power, Prosperity, and Poverty - Acemoglu, Daron and Robinson, James A (GHQ, Rawalpindi Services Book Club, 2012)
Why are some nations rich and others poor, divided by wealth and poverty, health and sickness, food and famine? Is it culture, the weather, geography, or perhaps ignorance of the right policies? Simply, no. None of these factors is either definitive or destiny. In this book the authors show that it is man-made political and economic institutions that underlie economic success (or lack of it). Based on fifteen years of original research, they marshall historical evidence from the Roman Empire to the Soviet Union, from Korea to Africa, to build a new theory of political economy with great relevance for the big questions of today, including: China has built an authoritarian growth machine. Will it continue to grow at such high speed and overwhelm the West? Is America moving from a virtuous circle, in which efforts by elites to aggrandize power are resisted, to a vicious one that enriches and empowers a small minority? What is the most effective way to help move billions of people from the rut of poverty to prosperity? Is it through more philanthropy from the wealthy nations of the West, or learning lessons on the interplay between inclusive political and economic institutions?
Include Maps, Illustrations, References, Bibliography and Index
Keywords: Economics Political Aspects -- Economic Development -- Social Policy -- Poverty